The Influence of Maternal Characteristics and Nutritional Status on Toddler Development: Literature Review - Nurul Fitriani; Rostika Flora; Mohammad Zulkarnain; Nur Alam Fajar; Elvi Sunarsih; Anita Rahmiwati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The first five years of a child's life are a time of peak development. According to the global prevalence, 52.9 million children under the age of five suffer from developmental problems. Parental involvement in monitoring their children's development will rise if parents have greater education, have a high level of knowledge, higher socioeconomic level, income, and the mother does not work. In addition, toddlers with good nutritional status will optimise their development. Objective: This literature review aims to identify how maternal characteristics and nutritional status impact toddler development. Method: This study is a systematic review by searching the literature through Google Scholar, Science Direct, and PubMed. Articles in Indonesian and English published from 2016 to 2022. Article searches used keywords or Boolean operators (AND - OR), some of the keywords used to search the literature included combinations of “development” OR “education” OR “income”’ OR “knowledge” OR “occupation” OR “nutritional status”, “education” AND “development”, “income” AND “development”, “knowledege” AND “development”, “occupation” AND “development”, “nutritional sataus” AND “development”. Result: The results of this study showed that maternal characteristics such as education level, knowledge, occupation, and family income, as well as nutritional status affect the development of toddlers. Conclusion: Knowing the interaction between maternal role and nutritional status can help optimise the development of toddlers according to their age.